Imperata cylindrica L. Rhizome: Network pharmacology and molecular docking analysis of active ingredients and their mechanisms of action in treating acute kidney injury - Rizal Dzulfaqaar Alauddin Daffa; Madyastuti Purwono Rini; Harlina Eva; Safithri Mega; Widyastuti Rini (BIO Web of Conferences)
Acute kidney injury (AKI) is a significant health concern that can result in kidney impairment and failure. Imperata cylindrica L., a traditional medicinal plant, has shown potential in treating renal diseases, though its mechanisms in AKI remain unclear. This research integrated network pharmacology and molecular docking to analyze the active constituents of Imperata cylindrica rhizome in relation to AKI treatment. Pharmacological databases were used to identify the active compounds and their therapeutic targets, while Venny 2.1.0 was employed to determine the common targets shared with AKI-related drugs. A protein–protein interaction (PPI) network was generated to illustrate target associations. ShinyGo was utilized to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. Molecular docking assessed the binding affinity and stability of active compounds with core targets. Key compounds, including 6-Methoxyflavone, Beta-Sitosterol, Bifendate, Luteolinidin, and Stigmasterol, were identified alongside 131 core targets. The docking results indicated strong binding interactions, suggesting therapeutic potential. These results offer valuable insight into the molecular mechanisms of I. cylindrica in AKI treatment, emphasizing the importance of further in vivo studies to validate its clinical effectiveness.